2002
DOI: 10.1126/science.1078535
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Dense Lithium

Abstract: Superconductivity in compressed lithium is observed by magnetic susceptibility and electrical resistivity measurements. A superconducting critical temperature (Tc) is found ranging from 9 to 16 kelvin at 23 to 80 gigapascals. The pressure dependence of Tc suggests multiple phase transitions, consistent with theoretical predictions and reported x-ray diffraction results. The observed values for Tc are much lower than those theoretically predicted, indicating that more sophisticated theoretical treatments simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
152
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(171 citation statements)
references
References 14 publications
15
152
4
Order By: Relevance
“…These features are consistent with the picture that reduced coordination numbers at high pressures arise from a Jahn-Teller-like distortion [2]. Calculations of the high-pressure phases also show an accumulation of electronic charge density within the interstitial region as the 2s electron density is pushed away from the atomic cores by Coulomb repulsion, Pauli exclusion, and the orthogonality of core and valence orbitals [2,3,5].Experiments suggest another phase transition at 60-70 GPa, although the new structure has not been determined [6,7]. A number of theoretical studies have sought to identify candidate phases at higher pressures [2,8,9].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…These features are consistent with the picture that reduced coordination numbers at high pressures arise from a Jahn-Teller-like distortion [2]. Calculations of the high-pressure phases also show an accumulation of electronic charge density within the interstitial region as the 2s electron density is pushed away from the atomic cores by Coulomb repulsion, Pauli exclusion, and the orthogonality of core and valence orbitals [2,3,5].Experiments suggest another phase transition at 60-70 GPa, although the new structure has not been determined [6,7]. A number of theoretical studies have sought to identify candidate phases at higher pressures [2,8,9].…”
mentioning
confidence: 94%
“…This structure contains sixfold coordinated atoms. On the other hand, recent hightemperature DFT molecular dynamics simulations found fourfold coordinated Li atoms in the pressure range 150-810 GPa [10].Superconductivity has been observed in Li up to $85 GPa, indicating metallic behavior [6,11,12]. However, calculations have suggested that semimetallic or even semiconducting behavior might occur at high pressures [2].…”
mentioning
confidence: 97%
“…Early high-pressure experiments [9] revealed a drop of resistivity in Li at 7 K between 22 and 32 GPa but the data were not conclusive enough to be interpreted in terms of superconductivity. Only recent measurements of electrical transport and magnetic properties have unambiguously shown that superconductivity exists in Li at pressures above 20 GPa and at temperatures up to 20 K [10,11,12]. The large interest in the superconductivity in dense lithium is also motivated by the fact that it is the "simplest" metal with only one valence electron, no d-electrons in sight, and it is the superconducting element closest to hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Elemental lithium, with superconducting T c ∼ 15 K around [1,2,3] 30 GPa and up to 20 K in strained samples [1] at 50 GPa, joins MgB 2 (T c =40 K), metallic Y (T c =20 K) [4], and PuCoGa 5 (T c =19 K) [5] as the big surprises in critical temperature in this century. Transformation from a simple nearly-free-electron metal not superconducting [6] above 100 µK to a strongly coupled electron-phonon superconductor at 20-50 GPa has been explained, at least semiquantitatively, in recent work by Profeta et al [7] and by Kasinathan et al [8].…”
Section: Introductionmentioning
confidence: 99%